Highly Contaminated Marine Sediments Can Host Rare Bacterial Taxa Potentially Useful for Bioremediation - Dell’Anno, Filippo; Rastelli, Eugenio; Tangherlini, Michael; Corinaldesi, Cinzia; Sansone, Clementina; Brunet, Christophe; Balzano, Sergio; Ianora, Adrianna; Musco, Luigi; Montereali, Maria Rita; Dell’Anno, Antonio (Frontiers in Microbiology, 2021)
Coastal areas impacted by high anthropogenic pressures typically display sediment contamination by polycyclic aromatic hydrocarbons (PAHs) and heavy metals (HMs). Microbial-based bioremediation represents a promising strategy for sediment reclamation, yet it frequently fails due to poor knowledge of the diversity and dynamics of the autochthonous microbial assemblages and to the inhibition of the target microbes in the contaminated matrix. In the present study, we used an integrated approach including a detailed environmental characterisation, high-throughput sequencing and culturing to identify autochthonous bacteria with bioremediation potential in the sediments of Bagnoli-Coroglio (Gulf of Naples, Mediterranean Sea), a coastal area highly contaminated by PAHs, aliphatic hydrocarbons and HMs. The analysis of the benthic prokaryotic diversity showed that the distribution of the dominant taxon (Gammaproteobacteria) was mainly influenced by PAHs, As and Cd concentrations. The other abundant taxa (including Alphaproteobacteria, Deltaproteobacteria, Bacteroidetes, Acidobacteria, Actinobacteria, NB1-j, Desulfobacterota, and Myxococcota) were mainly driven by sediment grain size and by Cu and Cr concentrations, while the rare taxa (i.e., each contributing <1%) by As and aliphatic hydrocarbons concentrations and by sediment redox potential. These results suggest a differential response of bacterial taxa to environmental features and chemical contamination and that different bacterial groups may be inhibited or promoted by different contaminants. This hypothesis was confirmed by culturing and isolating 80 bacterial strains using media highly enriched in PAHs, only 9 of which were contextually resistant to high HM concentrations. Such resistant isolates represented novel Gammaproteobacteria strains affiliated to Vibrio, Pseudoalteromonas and Agarivorans, which were only scarcely represented in their original assemblages. These findings suggest that rare but culturable bacterial strains resistant/tolerant to high levels of mixed contaminants can be promising candidates useful for the reclamation by bioaugmentation strategies of marine sediments that are highly contaminated with PAHs and HMs.